Influence of end groups in hyperbranched polyesters used as modifiers in the characteristics of epoxy thermosets cured by adipic dihydrazide - A. Serra; A. M. Tomuta; X. Ramis; S. De la Flor (eXPRESS Polymer Letters, 2013)
Mixtures of diglycidylether of bisphenol A (DGEBA) resin and different ratios of aliphatic-aromatic hyperbranched polyester (HBP) were cured by a latent curing agent, adipic dihydrazide (AH). The HBPs prepared have hydroxyl groups or 10-undecenoyl or allyl groups as chain ends. The curing mixtures were investigated by differential scanning calorimetry (DSC) to study the curing process and to evaluate the kinetic parameters of the different formulations. These studies suggest that HBPs decrease the curing rate of epoxy/AH in the case of vinyl terminated HPB, whereas OH terminated HBP accelerates the first stages and delays the lasts. The thermosets obtained showed an improvement in microhardness and impact strength without any reduction of the Tg and thermal parameters. Microparticle phase separation was observed with the undecenoyl HBP derivatives or when a 10% of allyl HBP derivative was in the formulation.